If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -4 = -60 Reorder the terms: -4 + -7x = -60 Solving -4 + -7x = -60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -7x = -60 + 4 Combine like terms: -4 + 4 = 0 0 + -7x = -60 + 4 -7x = -60 + 4 Combine like terms: -60 + 4 = -56 -7x = -56 Divide each side by '-7'. x = 8 Simplifying x = 8
| 23+17x+1=22x+4 | | x+70=36 | | 18x^3-9x^2-2x= | | 22x+4-17x+1=32 | | 3v^2+5x-8x=0 | | 17x+1+23=22x-4 | | 22x-4-(7x+1)=23 | | -16=-4x+7x-7 | | x+10y=0 | | -40=-7x+3x+8 | | -b^2+6b+7=0 | | 5x+3=3+9x | | 22x+4=23+7x+1 | | X=(-20/(e^(.1x))) | | 7x+1+23=22x+4 | | x(-14)=112 | | (7x+1)+23=22x+4 | | 7y+8-5+6y=9 | | 3x-12=-6+x | | (y+14)+y=32 | | 4s+2=16 | | 2(k+16)=72 | | (7+8)-(5+6y)=9 | | -4x+83=-80 | | 11=5+3y | | 5x+4=7x+4 | | 80=y | | 11=19-2b | | (2x-80)=x | | -2x-28=67-7x | | (5a-3)(5a-3)= | | 2x/x-9-x/2(x-9)= |